(untitled) (Praxis Educativa, 2026)
Spanish writing represents a complex process since linguistic norms are contemplated and which are adapted to grammatical, syntactic, semantic aspects, etc. One way of assessing the performance of this competence is by evaluating under the error analysis method. This investigation is framed in a quantitative methodology with a descriptive approach under corpus linguistics and error analysis to identify which are the most frequent errors in Spanish writing by undergraduate students and to verify whether evaluation really impacts the performance of such skill. Findings note that the most frequent errors are those with a spelling and punctuation nature and that the evaluation component does have an influence on Spanish writing performance. Thus, the evaluation enjoys a prominent position since it places the student in a conscious and responsible role before the challenges proposed in the classroom.